2017
DOI: 10.1080/87565641.2017.1334783
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar Contributions to Language in Typical and Atypical Development: A Review

Abstract: In this review, we present the growing literature suggesting, from a variety of angles, that the cerebellum contributes to higher-order cognitive functions, rather than simply sensorimotor functions, and more specifically to language and its development. The cerebellum’s association with language function is determined by the specific cortico-cerebellar connectivity to the right cerebellum from the left cortical hemisphere. The findings we review suggest that the cerebellum plays an important role as part of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 78 publications
1
30
0
Order By: Relevance
“…First, this may not be a direct association (i.e., more total sedentary time), but an indirect influence (lower physical activity levels) affecting the key role that the cerebellum has in motor control and movement [43][44][45]. Second, the importance of the cerebellum for intelligence has been previously reported in some populations, and the specific association with crystallized, rather than fluid, intelligence may be supported by previous functional imaging studies showing cerebellar activation in relation to language, attention and mental imagery [46][47][48]. However, in the present study we showed structural, but not functional, brain correlates of sedentary behaviors, and all these speculations about links with intelligence should be viewed with caution.…”
Section: Discussionmentioning
confidence: 60%
“…First, this may not be a direct association (i.e., more total sedentary time), but an indirect influence (lower physical activity levels) affecting the key role that the cerebellum has in motor control and movement [43][44][45]. Second, the importance of the cerebellum for intelligence has been previously reported in some populations, and the specific association with crystallized, rather than fluid, intelligence may be supported by previous functional imaging studies showing cerebellar activation in relation to language, attention and mental imagery [46][47][48]. However, in the present study we showed structural, but not functional, brain correlates of sedentary behaviors, and all these speculations about links with intelligence should be viewed with caution.…”
Section: Discussionmentioning
confidence: 60%
“…The co-activation patterns of lobule VI suggest that it also contributes to cognitive aspects of language processes together with frontoparietal regions (Stoodley et al, 2012;Vias and Dick, 2017). The inferior parietal lobe (IPL) and S1 (area 2) are tightly interconnected (Borich et al, 2015) and serve as an interface to process proprioceptive signals and body-related information (Prevosto et al, 2011;Tsakiris et al, 2007).…”
Section: Enhanced Dai Connectivity In Singers Versus Non-singersmentioning
confidence: 99%
“…The thalamus functions as a sort of relay center to connect many brain areas involved in language processing (Wahl et al, 2008;Murdoch, 2010;David et al, 2011) and changes in the thalamus have been claimed to contribute to the evolutionary emergence of our language-ready brain (see Boeckx and Benítez-Burraco, 214a for details). Similarly, the cerebellum plays a key role in language processing and is impaired in language-related pathologies (Vias and Dick, 2017;Mariën and Borgatti 2018). People with WS exhibit cerebellar volume alterations that are seemingly associated with their cognitive, affective and motor distinctive features (Osório et al, 2014).…”
Section: Resultsmentioning
confidence: 99%